Analisis Efisiensi Pemasaran Tandan Buah Segar (TBS) Kelapa Sawit (Studi Kasus di Desa Tanjung Aur Kecamatan Kikim Tengah Kabupaten Lahat) - Indra Hartini (Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine the marketing efficiency of fresh fruit bunches on oil palm commodities. South Sumatra Province is the sixth largest producer of palm oil in Indonesia. The data in this study were taken through a case study in the Tanjung Aur village area, Lahat district, South Sumatra province with the calculation of the land area from 2016 to 2020 with oil palm farmers as the main livelihood. Regarding the declining Oil palm fresh fruit bunch (FFB) price, the people of Tanjung Aur Village are restless and become an important problem point. One of the factors determining the price of FFB is the length of the marketing chain, which causes the profits received by farmers to be smaller. The data collection method in this study consisted of primary data and secondary data. Primary data were obtained through direct interviews with farmers, traders and consumers using a questionnaire. Secondary data is data taken from related agencies. Currently, the price of FFB for 2021 has increased by Rp. 2,272 per kilogram. In marketing FFB, farmers cannot directly market their harvests to processing factories but must go through collectors so that the margin is quite large. Farmers who want to get a suitable profit, farmers must break the marketing chain and sell their crops directly to the factory and no longer rely on existing marketing channels in the area.